Anxiety among student nurses in the Philippines: A gender and year-level analysis and its contributing factors in the COVID-19 context - Florence L. Pulido; Richelle Faith D. Cayabyab; Allura Xandra M. Adversalo; Alyssa V. Baylon; Aubrey N. Centeno; Aea Jainey G. Dizon; Marc Andrei L. Formoso; Alexis Angel P. Hernando; Eric Jon Luis B. Jucutan; Justine Anthonell G. Maltu; Daniel Joy R. Pia; Chaste Priel T. Sally; et al. (Belitung Raya Foundation, 2023)
Background: The shift to online learning during the COVID-19 pandemic has raised concerns and heightened anxiety levels, especially among student nurses adapting to academic and clinical challenges. Objective: This study aimed to assess the anxiety levels of student nurses during the COVID-19 pandemic, examining gender and year-level differences and identifying contributing factors. Methods: A quantitative descriptive research design was employed, involving 305 student nurses from Levels 1 to 4, selected using proportionate stratified and systematic random sampling at a Philippine nursing school. Data were collected in March 2022 using the Beck Anxiety Inventory (BAI) and a self-made questionnaire. Descriptive and inferential statistics, including frequencies, percentages, means, Independent t-tests, and ANOVA, were utilized with a significance level of 0.05. Results: The mean anxiety level among student nurses was 1.61, significantly differing by year level and gender (p <0.05). The most contributing factor of anxiety was 'the adjustments to make with the sudden change of face-to-face classes to online or distance learning mode' (90.16%), while the least factor was 'lack of financial sources' (46.23%). Conclusion: Student nurses had moderate anxiety levels, with gender and year level as significant contributing factors. Female student nurses experienced higher anxiety levels than males, and lower-level students experienced greater anxiety than their higher-level counterparts. Various factors, including academic, social, financial, and perceived health risk-related factors, affected student nurses' anxiety levels, with academic-related factors having the most significant impact and financial-related factors having the least impact.